The Effect of Dow Jones Industrial Average, Nikkei 225 Index and Shanghai Composite Index on IDX Composite Index - Elfiswandi Elfiswandi; Sunaryo Sunaryo; Muhammad Fikri Ramadhan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2021)
The purpose of this study is to determine the effect of the Dow Jones Industrial Average, the Nikkei 225 index and the Shanghai Composite Index on IDX Composite Index. The population and samples used in this study are the Dow Jones Industrial Average, the Nikkei 225 Index, the Shanghai Composite Index, and the IDX Composite Index for the period January 2 to April 30, 2020. The type of data is secondary data. The analysis method used are classical assumption test which consists of normality test, multicollinearity test and autocorrelation test and multiple regression analysis. Hypothesis test using F-test and t-test. The results of the study found that the Dow Jones Industrial Average and the Nikkie 225 index partially affected the IDX Composite Index positively and significantly. The Shanghai Composite Index has no significant effect on IDX Composite Index.